Thermal Analysis of Combustible Components of Municipal Solid Waste - Snezhkin Yu.F.; Mykhailyk V.A.; Korinchevska T.V. (Problems of the Regional Energetics)
The use of municipal solid waste as a raw material for alternative fuel is a promising direction for waste recycling and substitution of solid fossil fuels. Therefore, selecting of fuel composition and studying of its properties is an urgent task. The aim of this work is thermal characteristics analysis of the combustible components of municipal solid waste, which are the most common in Ukraine, for further selection of a fuel composition that will satisfy the consumer's requirements. The goal is achieved by studying the thermal destruction of samples by thermogravimetry and differential thermal analysis when materials are heated to 1000 ºС in the presence of air oxygen. Paper, cardboard, plastic, biodegradable film, textiles, leather, wood were investigated in this work. The most important results are the received data on the characteristic temperatures of destruction stages, content of water, organic and mineral substances, ash, as well as the calculated values of rate and conditional thermal effect of decomposition of organic substances. Strong formation of gaseous substances was registered for samples of polyethylene and biodegradable film, polyethylene terephthalate and cotton fabric. These features should be considered in the technologies of production and combustion of fuel. The significance of the results also lies in the fact that it is recommended to use data on the thermal stability of materials in order to prevent their ignition during drying when developing fuel production technology. In addition, the calculated values of the conditional thermal effect made it possible to evaluate the thermal characteristics of the studied materials as components of solid alternative fuels.